Effects of nursing intervention programs for women with gestational diabetes: a systematic review of randomized controlled trials - JooHee Kim; ChaeWeon Chung (Korean Society of Women Health Nursing, 2021)
Purpose This study aimed to identify the effects of nursing intervention programs for women with gestational diabetes mellitus (GDM) through a critical review of recent studies. Methods Studies related to effects of nursing intervention programs for women with GDM published in English or Korean between 2000 and 2019 were extracted from 10 electronic databases. The quality of the studies was evaluated and double-checked for accuracy by two reviewers using the Revised Cochrane Risk-of-Bias tool for randomized controlled trials. Results Twenty studies were selected, of which 19 had a low risk of bias and one had a high risk of bias. Interventions fell into six main groups: (1) integrated interventions, (2) self-monitoring of blood glucose levels, (3) dietary interventions, (4) exercise, (5) psychotherapy, and (6) complementary therapy. This review found that nursing interventions for GDM were of many types, and integrated interventions were the most common. However, low-carbohydrate diets and blood glucose monitoring interventions did not show statistically significant results. Evidence shows that various nursing intervention programs applied to GDM improved diverse aspects of maternal, fetal, and neonatal health, including both physical and psychological aspects. Conclusion The composition and delivery of integrated interventions continue to evolve, and these interventions affect physical and psychological indicators. Although interventions affecting physical health indicators (e.g., blood glucose levels, diet, and exercise) are important, many studies have shown that programs including psycho-emotional nursing interventions related to anxiety, depression, stress, self- efficacy, and self-management are also highly useful.